Technological implementations in the functional assessment and short performance test Short Physical Performance Battery (SPPB) for the elderly - Vargas-Del-Valle, María Cristina (2022)
The aim of this study is to implement technological resources in the design of a measurement system for the application of the Short Physical Performance Battery (SPPB) test in order to reduce the application time and increase the reliability of the measure. Product design and innovation methodologies in medical devices were used to develop a technological system appropriate to the characteristics of those involved in the process (rehabilitation therapists, geriatric doctors and elderly patients). In addition, a protocol and methodology was proposed to implement the test with the measurement system developed in the process established by health specialists who attend to the elderly population in Costa Rican health centers.